Just-ish? An analysis of routes to justice in family law disputes in England and Wales. Issue 3 (23rd October 2020) - Speed, Ana
Abstract: It is widely documented that the formal family justice system in England and Wales is in crisis. The family courts are plagued by delays and backlogs, whilst parties struggle to secure access to advice and representation due to cuts to public funding. Increasingly, litigants face economic, physical and cultural barriers to courts brought about by rising court fees, reforms to the court system and demographic changes which have resulted in diverse family forms for whom the family courts may have little legitimacy. The first part of this article examines how recent changes to family law and policy in England and Wales have reduced the ease with which parties are able to achieve procedural and substantive justice through the family courts. The second part of the article analyses how forums of dispute resolution which are delivered by non-state actors, but which rely on the state for their authority, have evolved to fill this justice gap and are therefore indicative of a move towards 'weak' legal pluralism in the context of family justice. It is argued that although the family courts are still an important cornerstone of the justice landscape, alternative forums of dispute resolution increasingly play a positive role in enabling disputants to achieve their procedural and substantive goals and this is strengthened by a weak approach to legal pluralism which upholds the autonomy of the parties whilst also ensuring necessary protections and safeguards for vulnerable litigants. The article therefore challenges critics of weak pluralism, who perceive that reliance on state recognition precludes institutions playing an important role outside of the state hierarchy.